Exploring the case of The White Moustache: Entrepreneurship and regulatory capture in the milk products industry. Issue 1 (10th April 2017) - Yonk, Ryan M.; Harris, Kayla; Martin, R. Chistopher; Anderson, Barrett
Abstract : Purpose: Small and emerging business failure rates are high for numerous reasons. Government regulation has been cited as a contributing factor, yet literature documenting the actual effects of government regulation on small business is limited. The purpose of this paper is to clearly outline the regulatory compliance costs and effects on small businesses in the California dairy industry. Design/methodology/approach: This paper applies a public choice framework to the history of dairy regulation and performs a case study on a small business, The White Moustache (TWM). The case study traces the burdens and costs of state dairy regulations placed on TWM as they sought the necessary permits to sell their artisan yogurt. Findings: Strict and unresponsive regulation restricted TWM from selling their product. To comply with state dairy regulations, the direct costs to TWM would have increased by 70 percent. In addition, regulation caused two and a half years of delay before the company decided to leave the state. California's dairy regulations place burdens on small dairy businesses that work as a strategic barrier to entry in the marketplace. Originality/value: This case study highlights the direct effects that strict and unresponsive regulation can have on entrepreneurs and emerging businesses through a case study. Improving the understanding of how regulation affects small business can highlight new paths forward and help improve the small business failure rate in the USA.